STUDI DESKRIPTIF ANALISIS MODIFIKASI DALAM HASIL PEMBELAJARAN KETERAMPILAN SEPAK TAKRAW - Viny Fitriana, - (2022)
The purpose of this study is to determine the application of facilities and infrastucture modification in the learning outcomes of sepak takraw. Descriptive analysis was used as the method of this research. The research sampling technique used was Purposive sampling. The sample used in this study were teachers of Physical Education, Sports and Health (PJOK) at SMAN 1 Jatiluhur. This study used questionnaire to collect the data. To analyze the data, this study used descriptive statistics. The results of the analysis show that the descriptive statistical data from 4 teachers who filled out the questionnaire of facilities and infrastucture modification showed the average number (Mean) = 139.5, Median = 141, Standard Deviation = 20.9, Variance = 436.3, minimum score = 115, maximum score = 161, and total score = 558. The application of game modification in the learning outcomes of sepak takraw showed that from 4 teachers, 1 teacher stated it was not effective (25%), 2 teachers stated it was effective (50%), and 1 teacher stated it was very effective (25%). Based on the results of the research on the application of facilities and infrastucture modification, modification is one of the options to achieve the overall learning outcomes, although with various problems, such as limited facilities and infrastructure at school. Then, most of the teachers concluded that the application of facilities and infrastructure modification in takraw skills learning was considered effective in the learning process at school and students could get learning outcomes as expected.